TAWAF DAN SIGOFI GAM POTRET KEARIFAN BUDAYA LOKAL KESULTANAN TERNATE BERDAMAI DENGAN COVID-19 - Ali Lating; Sarni Artha; Fathnun Tan (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2021)
North Maluku has a local culture that is rich with wisdom and intelligence. Local culture not only regulates governance, but is alsorelated to natural resource management, the environment and conflict management. The value of wisdom contained in the culture has a numberof meanings, especially those related to the safety and sustainability of its citizens. This paper tries to explain how local culture has wisdom,especially in preventing covid-19 in a number of areas of the Ternate Sultanate. A number of philosophical meanings that accompany theritual of tawaf and sigofi gam confirm a number of lessons such as the importance of maintaining the sustainability of local culture, safety ofcitizens, collaboration and collectivity between stakeholders to the importance of compliance in managing community life. Only bypreserving the local culture can the harmony and harmony of life between God and nature and respect for ancestors be realized